Carbon nanotube@nitrogen-doped mesoporous carbon@feconini alloy nanoparticle composite wave-absorbing material, preparation method and application thereof

CN122995116APending Publication Date: 2026-10-27HEBEI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611192653.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]为了解决碳纳米管基复合吸波材料存在的磁损耗不足与阻抗匹配难以协同调控等问题,本发明开发出一种以碳纳米管为一维导电骨架、以介孔聚多巴胺层为配位限域前驱层,并通过热处理原位形成FeCoNi合金纳米颗粒的复合吸波材料,来显著增强吸波材料的导电损耗、界面极化损耗、偶极极化损耗和磁损耗,改善阻抗匹配

Benefits of technology

[0025]另外,本发明也提供了如上所述碳纳米管@氮掺杂介孔碳@FeCoNi合金纳米颗粒复合吸波材料的应用,用作电磁屏蔽、雷达隐身、电磁防护或微波暗室中的吸波材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995116A_ABST
    Figure CN122995116A_ABST
Patent Text Reader

Abstract

The application discloses a carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite wave-absorbing material, which takes the carbon nanotube as a one-dimensional conductive framework, coats the carbon nanotube outer surface with a nitrogen-doped mesoporous carbon layer with mesoporous channels and metal ion coordination sites, and limits and distributes FeCoNi alloy nanoparticles in the nitrogen-doped mesoporous carbon layer or / and on the surface of the nitrogen-doped mesoporous carbon layer. The composite wave-absorbing material can improve impedance matching and enhance conductive loss, interface polarization loss, dipole polarization loss and magnetic loss, and is suitable for application in various electromagnetic pollution scenes such as electromagnetic shielding, radar stealth, electromagnetic protection, microwave darkroom and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of microwave absorbing materials technology, specifically to a carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite microwave absorbing material, as well as the preparation method and application of the composite microwave absorbing material. Background Technology

[0002] With the rapid development of modern communication and radar technologies towards higher frequencies and higher power, the space electromagnetic environment is becoming increasingly complex and severe. Electromagnetic interference (EMI) has become a key factor restricting the operational stability of high-end electronic equipment. At the same time, the extreme pursuit of payload and endurance by aerospace vehicles and portable electronic terminals has imposed stringent limitations on the lightweighting of integrated materials. In order to meet the dual requirements of "strong absorption" and "ultra-lightweight," the development of lightweight, efficient, and broadband electromagnetic wave absorbing materials has become a cutting-edge hot topic in academic research and industrial applications.

[0003] Carbon nanotubes (CNTs) have shown significant application potential in the field of electromagnetic absorption (EMA) materials due to their unique quasi-one-dimensional tubular structure, high aspect ratio, large specific surface area, and excellent conductivity. Furthermore, their conductive network and multiple scattering channels can synergistically provide dielectric loss, while their low density also meets the development requirements of lightweight absorbing materials. However, single-carbon nanotube systems generally suffer from problems such as excessively high dielectric constant, insufficient magnetic loss, and impedance mismatch, which limit further improvements in their broadband and high-intensity absorption performance.

[0004] To address the aforementioned bottlenecks, existing research largely focuses on composite synergistic modification strategies, but different technical routes still have their own unavoidable drawbacks. For example, a typical approach uses carbon nanotubes as templates to construct a hydrogenated graphite block interlayer via a 1,3,5-triacetylene coupling reaction, and then coats it with polydopamine followed by carbonization to obtain CNTs@HSGDY@NC nanofibers. Although this structure enhances interfacial polarization loss by forming a carbon / carbon heterostructure interface with the hydrogenated graphite block and nitrogen-doped carbon layer, its shortcomings are also obvious: First, the entire system relies solely on the dielectric loss mechanism and completely lacks magnetic components, with magnetic loss contribution being almost zero; second, due to the lack of magnetic response, the material cannot effectively adjust the complex permeability over a wide bandwidth, and impedance matching heavily relies on the single control of the dielectric constant, resulting in a narrowed absorption peak, limited effective absorption bandwidth, and difficulty in achieving a synergistic effect between absorption intensity and bandwidth, with overall performance far from meeting the requirements of wideband high efficiency. Another type of technology attempts to introduce magnetic components to compensate for the above shortcomings. For example, the publicly disclosed carbon nanotube / mesoporous carbon / metal oxide composite aerogel absorbing material has certain advantages in lightweight structural design, but its actual performance has significant shortcomings: On the one hand, its mesoporous carbon layer is prepared from a specific precursor, resulting in insufficient pore order and development, limited specific surface area and pore volume, weakening dielectric relaxation strength and multiple reflection loss capability, and making it difficult to finely control the dielectric constant; on the other hand, the loaded metal oxide particles are prone to agglomeration during sol-gel and heat treatment processes, resulting in uneven dispersion of magnetic particles, effective permeability far lower than theoretical value, and low magnetic loss efficiency. More importantly, the synergistic control between dielectric and magnetic components has not been effectively achieved, resulting in a narrow impedance matching window and an imbalance in the absorption performance of the material in the low-frequency and high-frequency ranges. Moreover, the material is an aerogel bulk, with complex molding process and poor mechanical strength, further limiting its practical application prospects. It is evident that while the two technical approaches described above each have their own unique characteristics, they are both limited by core issues such as lack of magnetic loss or poor dielectric-magnetic synergy and uneven particle dispersion, and urgently require new structural designs to overcome these bottlenecks.

[0005] Therefore, developing a composite microwave absorbing material with carbon nanotubes as the conductive framework is necessary to address the shortcomings of existing carbon nanotube-based composite microwave absorbing materials, such as insufficient magnetic loss, easy agglomeration of metal particles, and difficulty in synergistic control of impedance matching. This will have a positive promoting effect on the development and application of electromagnetic wave absorbing materials. Summary of the Invention

[0006] To address the issues of insufficient magnetic loss and difficulty in synergistic control of impedance matching in carbon nanotube-based composite microwave absorbing materials, this invention develops a composite microwave absorbing material that uses carbon nanotubes as a one-dimensional conductive framework, a mesoporous polydopamine layer as a coordination confinement precursor layer, and FeCoNi alloy nanoparticles formed in situ through heat treatment. This significantly enhances the conductive loss, interfacial polarization loss, dipole polarization loss, and magnetic loss of the microwave absorbing material, thereby improving impedance matching.

[0007] The carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite microwave absorbing material of the present invention uses carbon nanotubes as a one-dimensional conductive framework, and a nitrogen-doped mesoporous carbon layer with mesoporous channels and metal ion coordination sites is coated on the outer surface of the carbon nanotubes. FeCoNi alloy nanoparticles are confined and distributed in the nitrogen-doped mesoporous carbon layer and / or on its surface.

[0008] The composite microwave absorbing material of the present invention forms a nitrogen-doped mesoporous carbon layer with mesoporous channels and metal ion coordination sites on the outer surface of a one-dimensional conductive framework of carbon nanotubes. This layer serves as a confined shell for distributing FeCoNi alloy nanoparticles, achieving organic synergy among the three structures: carbon nanotubes, nitrogen-doped mesoporous carbon layer, and FeCoNi alloy nanoparticles. This results in maintaining lightweight characteristics while also considering dielectric loss, magnetic loss, and impedance matching, thereby enhancing the electromagnetic loss of the microwave absorbing material and improving impedance matching.

[0009] As a limitation of the above technical solution, the composite microwave absorbing material is prepared by forming a mesoporous polydopamine layer on the surface of functionalized carbon nanotubes through dopamine self-polymerization. Fe ions, Co ions and Ni ions are simultaneously confined and complexed by the mesoporous polydopamine layer to obtain the CNT@mesoPDA-M precursor. Finally, it is prepared by freeze drying and then two-step heat treatment at 300~380 ℃ and 700~900 ℃ respectively. The functionalized carbon nanotubes are functionalized by introducing oxygen-containing functional groups, namely carboxyl and hydroxyl groups, onto the surface of the carbon nanotubes; the mesoporous polydopamine layer is formed by the self-polymerization reaction of triblock copolymer F127, trimethylbenzene, and dopamine hydrochloride.

[0010] Functionalized carbon nanotubes with oxygen-containing functional groups such as carboxyl and hydroxyl groups introduced on their surface serve as one-dimensional conductive pathways and the basis for interfacial bonding. Dopamine is then attached to the interface of the functionalized carbon nanotube surface to construct a mesoporous polydopamine layer, which provides pore structure, interfacial polarization, and a metal confinement environment. Fe, Co, and Ni ions are then confined by the mesoporous polydopamine layer, i.e., Fe, Co, and Ni metal ions are introduced simultaneously within the same nanoscale interface. FeCoNi alloy nanoparticles are then formed by in-situ alloying through two-step heat treatment and nitrogen-doped mesoporous carbon layer. This provides magnetic loss and forms a heterogeneous interface with the carbon shell, thereby achieving synergy among the three structures: carbon nanotubes, nitrogen-doped mesoporous carbon layer, and FeCoNi alloy nanoparticles.

[0011] As a limitation on the above technical solution, the preparation conditions for functionalized carbon nanotubes are as follows: Multi-walled carbon nanotubes were placed in a mixed acid solution of concentrated nitric acid and concentrated sulfuric acid, and after ultrasonic dispersion and static reaction, solid-liquid separation, washing and drying were performed to obtain functionalized carbon nanotubes. Preferably, the volume ratio of concentrated nitric acid to concentrated sulfuric acid in the mixed acid solution is 0.9~1.1:3; the volume ratio of multi-walled carbon nanotubes to the mixed acid solution is 1 g: 30~50 mL.

[0012] Functionalization treatment by mixed acid oxidation can introduce oxygen-containing functional groups such as carboxyl and hydroxyl groups on the surface of carbon nanotubes, thereby improving the dispersion stability of carbon nanotubes in the water / ethanol system and enhancing the interfacial adhesion of dopamine on the surface of carbon nanotubes, providing a basis for the continuous formation of subsequent mesoporous polydopamine layers and metal ion coordination.

[0013] As a limitation on the above technical solution, the preparation conditions of the mesoporous polydopamine layer are as follows: Functionalized carbon nanotubes were dispersed in water, and triblock copolymer F127, trimethylbenzene and ethanol were added and mixed evenly. Tris buffer was then added to adjust the pH to 8-11. Subsequently, dopamine hydrochloride was added to carry out interfacial oxidative self-polymerization, so that dopamine formed a mesoporous polydopamine layer with mesoporous channels on the surface of the functionalized carbon nanotubes, thus obtaining the CNT@mesoPDA system. Preferably, the ratio of functionalized carbon nanotubes to water is 50 mg: 80~90 mL; the ratio of triblock copolymer F127 to ethanol is 1.6 g: 80~85 mL; the volume ratio of trimethylbenzene to ethanol is 1: 50~55; and the mass ratio of triblock copolymer F127 to dopamine hydrochloride is 1: 1.0~1.3.

[0014] Triblock copolymer F127 was used as a micelle soft template to induce the formation of a mesoporous polydopamine shell along the outer surface of carbon nanotubes. Trimethylbenzene was used as a hydrophobic swelling agent to enter the hydrophobic region of F127 micelles and regulate the pore size. Ethanol was used as a co-solvent to facilitate the uniform dispersion and interfacial assembly of F127, trimethylbenzene and dopamine in the aqueous phase. Tris buffer provided a weakly alkaline environment to promote the oxidative self-polymerization of dopamine. The resulting mesoporous polydopamine layer can simultaneously have mesoporous channels and coordination sites, so that Fe ions, Co ions and Ni ions can efficiently complex with the coordination sites and be confined in the mesoporous polydopamine layer.

[0015] As a limitation of the above technical solution, the preparation conditions of the CNT@mesoPDA-M precursor are as follows: Iron salt, cobalt salt and nickel salt were added to the CNT@mesoPDA system and the reaction was stirred thoroughly to obtain the CNT@mesoPDA-M precursor; Preferably, the ratio of the mass of functionalized carbon nanotubes to the total molar amount of iron, cobalt and nickel salts is 50 mg: 0.5~2.0 mmol, and / or the molar ratio of iron, cobalt and nickel salts is Fe:Co:Ni=5:4:1.

[0016] The Fe component enhances magnetic response, the Co component improves magnetic anisotropy and natural resonance response, and the Ni component regulates the nucleation, growth, and stability of alloy particles. Under specific molar ratios, these three metal components, in conjunction with the coordination confinement effect of the mesoporous polydopamine layer, can form FeCoNi alloy nanoparticles on the outer surface of carbon nanotubes, creating a coupling interface with the nitrogen-doped mesoporous carbon layer.

[0017] As a limitation of the above technical solution, the two-step heat treatment conditions are as follows: under an Ar / H2 atmosphere, the temperature is increased to 300~380 ℃ at a rate of 1~3 ℃ / min and held for 1.5~2.5 h, and then increased to 700~900 ℃ at a rate of 2~4 ℃ / min and held for 2.5~3.5 h. Preferably, the FeCoNi alloy nanoparticles in the obtained composite microwave absorbing material have a particle size of 5~10 nm.

[0018] The CNT@mesoPDA-M precursor undergoes a two-step heat treatment under an Ar / H2 atmosphere to carbonize the mesoporous polydopamine layer into a nitrogen-doped mesoporous carbon layer. Simultaneously, Fe, Co, and Ni ions are reduced in situ within the nitrogen-doped mesoporous carbon layer and alloyed into FeCoNi alloy nanoparticles, resulting in a one-dimensional carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle powder microwave absorbing material.

[0019] The composite microwave absorbing material of the present invention has a mesoporous polydopamine layer that functions as a soft template replication, metal ion coordination, and confined reactor. Its coordination sites can simultaneously complex Fe ions, Co ions, and Ni ions, enabling the three metal ions to be distributed at the nanoscale on the outer surface of the carbon nanotubes. During the two-step heat treatment process, the mesoporous polydopamine layer is transformed into a nitrogen-doped mesoporous carbon layer, and the three metal ions are simultaneously reduced and alloyed into FeCoNi alloy nanoparticles.

[0020] Meanwhile, the present invention also provides a method for preparing the carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite microwave absorbing material as described above, comprising the following preparation steps: Step a: Add multi-walled carbon nanotubes to a mixed solution of concentrated nitric acid and concentrated sulfuric acid, sonicate at room temperature for 4-5 h, and let stand for 168-188 h; then centrifuge at 7000-11000 rpm for 8-10 min, wash with deionized water until neutral, and vacuum dry at 60-80 ℃ for 12-24 h to obtain functionalized carbon nanotubes (CNTs). Step b: Disperse the CNTs obtained in step a in deionized water and sonicate to form a uniform suspension; then add triblock copolymer F127, trimethylbenzene and ethanol in sequence and sonicate to mix evenly; then add Tris buffer solution with a concentration of 10~100 mM to adjust the pH of the reaction system to 8~11, and then slowly add dopamine hydrochloride. Stir the reaction at room temperature for 6~7 hours to form a mesoporous polydopamine layer and obtain CNT@mesoPDA. Step c: Weigh iron salt, cobalt salt and nickel salt according to the Fe, Co and Ni molar ratio, control the total molar amount of metal salt, add each metal salt to the CNT@mesoPDA system prepared in step b to react and form CNT@mesoPDA-M precursor. After the reaction is completed, filter, wash and freeze dry to obtain powdered CNT@mesoPDA-M precursor. In step d, the CNT@mesoPDA-M precursor powder was heated to 300-380 ℃ at 1-3 ℃ / min and held for 1.5-2.5 h, and then heated to 700-900 ℃ at 2-4 ℃ / min and held for 2.5-3.5 h to obtain a carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite microwave absorbing material.

[0021] The preparation of the composite absorbing material of this invention is simple and convenient, and does not require complex and harsh reaction conditions or pretreatment. It can obtain a structurally stable and high-performance absorbing material, which is of great significance for the application and promotion of the material.

[0022] As a limitation of the above technical solution, the iron salt in step c is preferably FeCl2·4H2O, the cobalt salt is preferably CoCl2·6H2O, and the nickel salt is preferably NiCl2·6H2O; the ratio of the mass of functionalized carbon nanotubes to the total molar amount of the metal salts iron, cobalt and nickel is preferably 50mg:1.0~1.5 mmol.

[0023] As a limitation on the above technical solution, the preferred conditions for the preparation method are: Step a: Take 1 g of multi-walled carbon nanotubes and add 40 mL of a mixed solution prepared by concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:3. After sonicating at room temperature for 4 h, let stand for 168 h. Then, centrifuge at 8000 rpm for 10 min, wash with deionized water until neutral, and vacuum dry at 60 ℃ for 12 h to obtain functionalized carbon nanotubes (CNTs). In step b, 50 mg of the CNTs prepared in step a were dispersed in 80 mL of deionized water and sonicated for 2 h to form a homogeneous suspension. Then, 1.6 g of triblock copolymer F127, 1.6 mL of trimethylbenzene, and 80 mL of ethanol were added sequentially and sonicated for 1 h to mix evenly. Subsequently, 10 mM Tris buffer was added dropwise to adjust the pH of the reaction system to 8.5, and then 1.8 g of dopamine hydrochloride was slowly added. The mixture was stirred at room temperature for 6 h to form a mesoporous polydopamine layer, thus obtaining CNT@mesoPDA. Step c: Weigh the metal salts FeCl2·4H2O, CoCl2·6H2O and NiCl2·6H2O in a molar ratio of Fe:Co:Ni=5:4:1, controlling the total molar amount of the metal salts to be 1 mmol. Add each metal salt to the CNT@mesoPDA system prepared in step b to react and form the CNT@mesoPDA-M precursor. After the reaction is complete, filter, wash and freeze-dry for 24 h to obtain the powdered CNT@mesoPDA-M precursor. Step d: The CNT@mesoPDA-M precursor powder was heated to 350 ℃ at 1 ℃ / min and held for 2 h in an Ar / H2 atmosphere, and then heated to 700 ℃ at 2 ℃ / min and held for 3 h to obtain a mesoporous carbon-coated carbon nanotube material loaded with FeCoNi alloy nanoparticles, which is the carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite microwave absorbing material CNT@mesoC@FeCoNi.

[0024] Further improve and optimize the preparation process to enhance the performance of composite microwave absorbing materials.

[0025] In addition, the present invention also provides the application of the carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite absorbing material as described above, for use as an absorbing material in electromagnetic shielding, radar stealth, electromagnetic protection or microwave anechoic chambers.

[0026] In summary, the carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite microwave absorbing material of the present invention has the following beneficial effects in its preparation and application methods.

[0027] First, a mesoporous polydopamine layer is formed by assembling a triblock copolymer F127 / trimethylbenzene / dopamine interface, enabling the carbon nanotube surface to simultaneously acquire a continuous mesoporous shell and metal ion coordination sites. Second, through the simultaneous complexation and confined thermal reduction of Fe, Co, and Ni ions by the mesoporous polydopamine layer, the ternary metal components are in-situ alloyed on the outer surface of the carbon nanotube, reducing the risk of migration and aggregation of FeCoNi alloy nanoparticles during high-temperature processing. Third, the multi-interface coupling structure formed by one-dimensional carbon nanotubes, nitrogen-doped mesoporous carbon layers, and FeCoNi alloy nanoparticles can enhance conductivity loss, interfacial polarization loss, dipole polarization loss, and magnetic loss, and improve impedance matching, making it suitable for applications in various electromagnetic pollution scenarios such as electromagnetic shielding, radar stealth, electromagnetic protection, and microwave anechoic chambers. Attached Figure Description

[0028] Figure 1 Two-dimensional reflection loss spectrum of CNT@mesoC@FeCoNi composite material FCN-1 prepared in Example 1 as a function of frequency and thickness.

[0029] Figure 2 The image shows a SEM image of the CNT@mesoC@FeCoNi composite material FCN-2 prepared in Example 2.

[0030] Figure 3 The image shows a TEM image of the CNT@mesoC@FeCoNi composite material FCN-2 prepared in Example 2.

[0031] Figure 4 The two-dimensional reflection loss spectrum of the CNT@mesoC@FeCoNi composite material FCN-2 prepared in Example 2 varies with frequency and thickness.

[0032] Figure 5 The two-dimensional reflection loss spectrum of the CNT@mesoC@FeCoNi composite material FCN-3 prepared in Example 3 varies with frequency and thickness.

[0033] Figure 6 SEM image of CNTs prepared for Comparative Example 1.

[0034] Figure 7 This is a two-dimensional reflection loss spectrum of CNT prepared in Comparative Example 1 of the present invention, showing the variation of frequency and thickness.

[0035] Figure 8 SEM image of the CNT@mesoC composite material prepared in Comparative Example 2.

[0036] Figure 9 TEM image of the CNT@mesoC composite material prepared in Comparative Example 2.

[0037] Figure 10Two-dimensional reflection loss spectrum of CNT@mesoC composite material prepared for Comparative Example 2 as a function of frequency and thickness.

[0038] Figure 11 XRD patterns of the CNT@mesoC@FeCoNi composite materials prepared for the examples and the comparative examples of CNT and CNT@mesoC materials.

[0039] Figure 12 The two-dimensional RCS values ​​of the CNT@mesoC@FeCoNi composite materials prepared for the examples and the comparative CNT and CNT@mesoC materials at a specific detection angle. Detailed Implementation

[0040] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0041] Unless otherwise specified, the experimental methods used in the following examples and comparative examples are conventional methods.

[0042] In the quantitative experiments of the following examples and comparative examples, three replicate experiments were set up, and the average value of the results was taken.

[0043] Raw materials used: multi-walled carbon nanotubes with a diameter of 30-50 nm, a length of less than 10 μm, and a purity of 95%; 1,2,4-trimethylbenzene (TMB, purity 98%); concentrated nitric acid, concentrated sulfuric acid, nickel chloride hexahydrate, cobalt chloride hexahydrate, ferrous chloride tetrahydrate, triblock copolymer F127, dopamine hydrochloride, Tris, and anhydrous ethanol were all commercially available analytical grade reagents; the experimental solvent was deionized water.

[0044] Example 1 A carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite microwave absorbing material, abbreviated as CNT@mesoC@FeCoNi composite material, is prepared according to the following steps.

[0045] Step a: Take 1 g of multi-walled carbon nanotubes and add them to a 100 mL flask. Then add 40 mL of a mixed solution of concentrated nitric acid and concentrated sulfuric acid (the volume ratio of concentrated nitric acid to concentrated sulfuric acid in the mixed solution is 1:3). After sonicating at room temperature for 4 h, let it stand for 168 h to introduce carboxyl and hydroxyl oxygen-containing functional groups on the surface of carbon nanotubes. Then centrifuge at 8000 rpm for 10 min, wash with deionized water until neutral, and vacuum dry at 60 ℃ for 12 h to obtain functionalized carbon nanotubes (CNTs).

[0046] In step b, 50 mg of the CNTs prepared in step a were dispersed in 80 mL of deionized water and sonicated for 2 h to form a uniform suspension. Then, 1.6 g of triblock copolymer F127, 1.6 mL of trimethylbenzene and 80 mL of ethanol were added sequentially and sonicated for 1 h to mix evenly. Subsequently, 10 mM Tris buffer was added dropwise to adjust the pH of the reaction system to 8.5, and 1.8 g of dopamine hydrochloride was slowly added. The mixture was stirred at room temperature for 6 h to allow dopamine to undergo interfacial self-polymerization on the CNT surface to form a mesoporous polydopamine layer, thus obtaining CNT@mesoPDA.

[0047] Step c: Weigh the metal salts FeCl2·4H2O, CoCl2·6H2O, and NiCl2·6H2O in a molar ratio of Fe:Co:Ni = 5:4:1, controlling the total molar amount of the metal salts to be 1 mmol. Add each metal salt to the CNT@mesoPDA system prepared in step b to react, so that Fe ions, Co ions, and Ni ions can be simultaneously complexed and confined in the mesoporous polydopamine layer to form the CNT@mesoPDA-M precursor. After the dopamine self-polymerization reaction is completed, filter, wash with deionized water, and freeze-dry at -61 ℃ for 24 h to obtain the powdered CNT@mesoPDA-M precursor.

[0048] Step d: The CNT@mesoPDA-M precursor powder was placed in an alumina crucible and heated to 350 ℃ for 2 h at an Ar / H2 atmosphere at a rate of 1 ℃ / min. Then, the temperature was increased to 700 ℃ at a rate of 2 ℃ / min and held for 3 h to obtain a mesoporous carbon-coated carbon nanotube material loaded with FeCoNi alloy nanoparticles. This material is called carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite microwave absorbing material CNT@mesoC@FeCoNi, denoted as FCN-1.

[0049] Electromagnetic parameters were measured using the coaxial method, and the material reflection loss was calculated based on transmission line theory. The test results are as follows: Figure 1 As shown, FCN-1 with a fill amount of 20 wt.% and a matching thickness of 1.64 mm has a minimum reflection loss of -58.71 dB at 14.68 GHz and an effective absorption bandwidth of 5.84 GHz, i.e., 12.16~18 GHz.

[0050] Example 2 The CNT@mesoC@FeCoNi composite material of this embodiment is basically the same as that of Example 1 in terms of raw materials and preparation, except that the total molar amount of iron salt, cobalt salt and nickel salt used in step c is different, which is 1.5 mmol. The resulting composite material is denoted as FCN-2.

[0051] like Figure 2 and Figure 3As shown, FCN-2 maintains a one-dimensional structure, and the FeCoNi alloy nanoparticles have a particle size of 5~10 nm. The FeCoNi alloy nanoparticles are distributed in the mesoporous carbon layer on the carbon nanotube surface and / or on its surface, indicating that the mesoporous polydopamine layer plays a confinement role during the heat treatment process.

[0052] like Figure 4 As shown, FCN-2 with a filler content of 20 wt.% and a thickness of 2.38 mm has a reflection loss of -83.57 dB at 10.82 GHz and a maximum absorption bandwidth of 3.2 GHz, i.e., 9.4~12.6 GHz.

[0053] Example 3

[0054] The CNT@mesoC@FeCoNi composite material of this embodiment is basically the same as that of Example 1 in terms of raw materials and preparation, except that the total molar amount of iron salt, cobalt salt and nickel salt used in step c is different, which is 2 mmol. The resulting composite material is denoted as FCN-3.

[0055] like Figure 5 As shown, FCN-3 with a fill amount of 20 wt.% has a minimum reflection loss of -66.73 dB at 4.51 GHz when the matching thickness is 4.94 mm; and a maximum absorption bandwidth of 3.89 GHz, i.e., 5.70~9.59 GHz, when the thickness is 3.38 mm.

[0056] Examples 1-3 demonstrate that by fixing the Fe:Co:Ni molar ratio at 5:4:1 and adjusting the total molar amount of the ternary metal salt, the FeCoNi alloy particle content can be controlled, thus achieving frequency band control: FCN-1 is suitable for high-frequency absorption, FCN-3 exhibits low-frequency absorption characteristics, and FCN-2 with a total metal salt content of 1.5 mmol combines excellent absorption intensity with a wide effective absorption bandwidth. The three sets of test results confirm that CNT@PDA-FeCoNi composite materials prepared with a total metal salt content in the range of 1.0–2.0 mmol can all achieve effective electromagnetic wave absorption (RL ≤ -10 dB).

[0057] Comparative Example 1 This comparative example provides a functionalized carbon nanotube (CNT) prepared by the following method.

[0058] 1 g of multi-walled carbon nanotubes was added to a 100 mL flask, and 40 mL of a mixed solution of concentrated nitric acid and concentrated sulfuric acid was added, with a volume ratio of 1:3. The mixture was sonicated at room temperature for 4 h and then allowed to stand for 168 h to introduce carboxyl and hydroxyl oxygen-containing functional groups onto the surface of the carbon nanotubes. The mixture was then centrifuged at 8000 rpm for 10 min and separated. The nanotubes were washed with deionized water until neutral and then vacuum dried at 60 °C for 12 h to obtain functionalized carbon nanotubes (CNTs).

[0059] like Figure 6 As shown, CNTs have a slender and uniform tubular structure with a relatively smooth surface and no obvious coating or additional particles.

[0060] like Figure 7 As shown, the reflection loss performance of CNTs is limited, mainly relying on the dielectric loss of surface functional groups and carbon nanotubes themselves, indicating that functionalized carbon nanotubes alone cannot simultaneously meet the requirements of strong absorption and broadband absorption.

[0061] Comparative Example 2 This comparative example provides a CNT@mesoC composite material, and the specific preparation method is as follows.

[0062] Step a: Functionalized carbon nanotubes (CNTs) were prepared according to the method of Comparative Example 1.

[0063] In step b, 50 mg of CNT was dispersed in 80 mL of deionized water and sonicated for 2 h to form a homogeneous suspension. Then, 1.6 g of F127, 1.6 mL of trimethylbenzene, and 80 mL of ethanol were added sequentially, and the mixture was sonicated for 1 h to mix thoroughly. The pH was then adjusted to 8.5 by adding 10 mM Tris buffer dropwise, followed by the slow addition of 1.8 g of dopamine hydrochloride. The mixture was stirred at room temperature for 6 h. After the reaction was complete, the mixture was filtered, washed, and freeze-dried for 24 h to obtain a powdered precursor.

[0064] Step c: The precursor powder is placed in an alumina crucible and heated to 350℃ at 1℃ / min and held for 2 h under an Ar / H2 atmosphere. Then, the temperature is increased to 700℃ at 2℃ / min and held for 3 h to obtain CNT@mesoC, denoted as FCN-0.

[0065] like Figure 8 and Figure 9 As shown, the surface of the CNT@mesoC sample is no longer smooth and has a more obvious porous structure, indicating that mesoporous carbon was successfully coated on the surface of carbon nanotubes.

[0066] like Figure 10As shown, the CNT@mesoC sample, with a thickness of 3 mm, exhibits a minimum reflection loss of -13.5 dB at 8.17 GHz and an absorption bandwidth of 4.85 GHz, i.e., 6.15–11 GHz. Compared to Comparative Example 1, the mesoporous carbon coating introduces multiple scattering and interfacial polarization mechanisms, but due to the lack of magnetic loss components, its absorption intensity and effective absorption bandwidth are still lower than those of Examples 1 and 2.

[0067] XRD analysis was performed on the material samples prepared in each embodiment and comparative example, such as... Figure 11 As shown, the diffraction peak at 26° for each CNT@mesoC@FeCoNi composite sample corresponds to the (002) crystal plane of carbon nanotubes. Meanwhile, characteristic peaks of FeCoNi alloy appear at 44.7°, 66°, and 82.7°, indicating that the FeCoNi alloy has been loaded into the carbon matrix. In addition to the carbon nanotube diffraction peaks, the CNT@mesoC sample also shows broadening peaks related to mesoporous carbon, indicating that a mesoporous carbon shell has been formed. The presence of (002) crystal plane diffraction peaks in CNTs suggests that the functionalization process mainly introduces functional groups to the surface, while the main structure of the carbon nanotubes remains unchanged.

[0068] CST Studio Suite 2022 was used to model and analyze the radar cross section (RCS) of the material samples in each embodiment and comparative example under different incident angles, such as... Figure 12 As shown, within the angular range of -90° to 90°, at a frequency of 10.82 GHz, the RCS value of the CNT@mesoC@FeCoNi composite material is below -20 dBm. 2 At an incident angle of 6°, the RCS value reaches -45.75 dBm. 2 By calculating the RCS difference between the PEC substrate and the sample, the maximum reduction value of the composite coating exceeded 33.91 dBm. 2 .

[0069] As can be seen from Comparative Examples 1 and 2 and Examples 1-3, there is a synergistic effect among the functionalized carbon nanotubes, nitrogen-doped mesoporous carbon layers, and FeCoNi alloy nanoparticles: the functionalized carbon nanotubes provide a one-dimensional conductive pathway and a basis for interfacial bonding; the nitrogen-doped mesoporous carbon layers provide pore structure, interfacial polarization, and a metal confinement environment; and the FeCoNi alloy nanoparticles provide magnetic loss and form a heterogeneous interface with the carbon shell. These results demonstrate that the technical effectiveness of this invention stems from the overall technical chain of acid oxidation functionalization, F127 / trimethylbenzene-induced mesoporous polydopamine layer, simultaneous Fe / Co / Ni complexation confinement, and two-step heat treatment in-situ alloying.

[0070] In summary, the CNT@mesoC@FeCoNi composite absorbing material of the present invention can achieve high intensity and wide bandwidth electromagnetic wave absorption at a filling amount of 20 wt.%. In particular, Example 2, with a thickness of 2.38 mm, achieves a reflection loss of -83.57 dB at 10.82 GHz and a maximum absorption bandwidth of 5.55 GHz, showing good potential for engineering applications.

[0071] Please note that the technical features of the above embodiments can be combined arbitrarily. For the sake of brevity, not all possible combinations of the technical features in the above embodiments have been described. However, as long as the combination of these technical features does not contradict each other, it should be considered within the scope of this specification. The above embodiments only illustrate several implementation methods of this application, and their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of the invention patent. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.

Claims

1. A carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite microwave absorbing material, characterized in that: This composite microwave absorbing material uses carbon nanotubes as a one-dimensional conductive framework, with a nitrogen-doped mesoporous carbon layer having mesoporous channels and metal ion coordination sites coated on the outer surface of the carbon nanotubes, and FeCoNi alloy nanoparticles confined and distributed in the nitrogen-doped mesoporous carbon layer and / or on its surface.

2. The carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite microwave absorbing material according to claim 1, characterized in that: The composite microwave absorbing material is prepared by forming a mesoporous polydopamine layer on the surface of functionalized carbon nanotubes through dopamine self-polymerization. Fe ions, Co ions and Ni ions are simultaneously confined and complexed by the mesoporous polydopamine layer to obtain the CNT@mesoPDA-M precursor. Finally, it is prepared by freeze drying and then two-step heat treatment at 300~380 ℃ and 700~900 ℃ respectively. The functionalized carbon nanotubes are functionalized by introducing oxygen-containing functional groups, namely carboxyl and hydroxyl groups, onto the surface of the carbon nanotubes; the mesoporous polydopamine layer is formed by the self-polymerization reaction of triblock copolymer F127, trimethylbenzene, and dopamine hydrochloride.

3. The carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite microwave absorbing material according to claim 2, characterized in that, The preparation conditions for functionalized carbon nanotubes are as follows: Multi-walled carbon nanotubes were placed in a mixed acid solution of concentrated nitric acid and concentrated sulfuric acid, and after ultrasonic dispersion and static reaction, solid-liquid separation, washing and drying were performed to obtain functionalized carbon nanotubes. Preferably, the volume ratio of concentrated nitric acid to concentrated sulfuric acid in the mixed acid solution is 0.9~1.1:3; the volume ratio of multi-walled carbon nanotubes to the mixed acid solution is 1 g: 30~50 mL.

4. The carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite microwave absorbing material according to claim 3, characterized in that, The preparation conditions for the mesoporous polydopamine layer are as follows: Functionalized carbon nanotubes were dispersed in water, and triblock copolymer F127, trimethylbenzene and ethanol were added and mixed evenly. Tris buffer was then added to adjust the pH to 8-11. Subsequently, dopamine hydrochloride was added to carry out interfacial oxidative self-polymerization, so that dopamine formed a mesoporous polydopamine layer with mesoporous channels on the surface of the functionalized carbon nanotubes, thereby obtaining the CNT@mesoPDA system. Preferably, the ratio of functionalized carbon nanotubes to water is 50 mg: 80~90 mL; the ratio of triblock copolymer F127 to ethanol is 1.6 g: 80~85 mL; the volume ratio of trimethylbenzene to ethanol is 1: 50~55; and the mass ratio of triblock copolymer F127 to dopamine hydrochloride is 1: 1.0~1.

3.

5. The carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite microwave absorbing material according to claim 4, characterized in that, The preparation conditions for the CNT@mesoPDA-M precursor are as follows: Iron salt, cobalt salt and nickel salt were added to the CNT@mesoPDA system and the reaction was stirred thoroughly to obtain the CNT@mesoPDA-M precursor; Preferably, the ratio of the mass of functionalized carbon nanotubes to the total molar amount of iron, cobalt and nickel salts is 50 mg: 0.5~2.0 mmol, and / or the molar ratio of iron, cobalt and nickel salts is Fe:Co:Ni=5:4:

1.

6. The carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite microwave absorbing material according to claim 2, characterized in that, The two-step heat treatment conditions are as follows: under an Ar / H2 atmosphere, the temperature is increased to 300~380 ℃ at a rate of 1~3 ℃ / min and held for 1.5~2.5 h, and then increased to 700~900 ℃ at a rate of 2~4 ℃ / min and held for 2.5~3.5 h. Preferably, the FeCoNi alloy nanoparticles in the obtained composite microwave absorbing material have a particle size of 5~10 nm.

7. The method for preparing the carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite microwave absorbing material according to any one of claims 1 to 6, characterized in that, The preparation steps include the following: Step a: Add multi-walled carbon nanotubes to a mixed solution of concentrated nitric acid and concentrated sulfuric acid, sonicate at room temperature for 4-5 h, and let stand for 168-188 h; then centrifuge at 7000-11000 rpm for 8-10 min, wash with deionized water until neutral, and vacuum dry at 60-80℃ for 12-24 h to obtain functionalized carbon nanotubes (CNTs). Step b: Disperse the CNTs obtained in step a in deionized water and sonicate to form a uniform suspension; then add triblock copolymer F127, trimethylbenzene and ethanol in sequence and sonicate to mix evenly; then add Tris buffer solution with a concentration of 10~100 mM to adjust the pH of the reaction system to 8~11, and then slowly add dopamine hydrochloride. Stir the reaction at room temperature for 6~7 hours to form a mesoporous polydopamine layer and obtain CNT@mesoPDA. Step c: Weigh iron salt, cobalt salt and nickel salt according to the Fe, Co and Ni molar ratio, control the total molar amount of metal salt, add each metal salt to the CNT@mesoPDA system prepared in step b to react and form CNT@mesoPDA-M precursor. After the reaction is completed, filter, wash and freeze dry to obtain powdered CNT@mesoPDA-M precursor. In step d, the CNT@mesoPDA-M precursor powder was heated to 300-380 ℃ at 1-3 ℃ / min and held for 1.5-2.5 h, and then heated to 700-900 ℃ at 2-4 ℃ / min and held for 2.5-3.5 h to obtain a carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite microwave absorbing material.

8. The method for preparing the carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite microwave absorbing material according to claim 7, characterized in that: The iron salt in step c is preferably FeCl2·4H2O, the cobalt salt is preferably CoCl2·6H2O, and the nickel salt is preferably NiCl2·6H2O; the ratio of the mass of functionalized carbon nanotubes to the total molar amount of the iron, cobalt, and nickel salts is preferably 50 mg: 1.0~1.5 mmol.

9. The method for preparing the carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite microwave absorbing material according to claim 8, characterized in that, The preferred conditions for the preparation method are: Step a: Take 1 g of multi-walled carbon nanotubes and add 40 mL of a mixed solution prepared by concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:

3. After sonicating at room temperature for 4 h, let stand for 168 h. Then, centrifuge at 8000 rpm for 10 min, wash with deionized water until neutral, and vacuum dry at 60 ℃ for 12 h to obtain functionalized carbon nanotubes (CNTs). Step b: Disperse 50 mg of CNT obtained in step a in 80 mL of deionized water and sonicate for 2 h to form a uniform suspension; Then, 1.6 g of triblock copolymer F127, 1.6 mL of trimethylbenzene and 80 mL of ethanol were added sequentially, and the mixture was sonicated for 1 h to mix evenly. Subsequently, 10 mM Tris buffer was added dropwise to adjust the pH of the reaction system to 8.5, and then 1.8 g of dopamine hydrochloride was slowly added. The mixture was stirred at room temperature for 6 h to form a mesoporous polydopamine layer, thus obtaining CNT@mesoPDA. Step c: Weigh the metal salts FeCl2·4H2O, CoCl2·6H2O and NiCl2·6H2O in a molar ratio of Fe:Co:Ni=5:4:1, controlling the total molar amount of the metal salts to be 1 mmol. Add each metal salt to the CNT@mesoPDA system prepared in step b to react and form the CNT@mesoPDA-M precursor. After the reaction is complete, filter, wash and freeze-dry for 24 h to obtain the powdered CNT@mesoPDA-M precursor. Step d: The CNT@mesoPDA-M precursor powder was heated to 350 ℃ at 1 ℃ / min and held for 2 h in an Ar / H2 atmosphere, and then heated to 700 ℃ at 2 ℃ / min and held for 3 h to obtain a mesoporous carbon-coated carbon nanotube material loaded with FeCoNi alloy nanoparticles, which is the carbon nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite microwave absorbing material CNT@mesoC@FeCoNi.

10. The application of the nanotube@nitrogen-doped mesoporous carbon@FeCoNi alloy nanoparticle composite microwave absorbing material according to any one of claims 1 to 6, characterized in that: Used as an absorbing material for electromagnetic shielding, radar stealth, electromagnetic protection, or microwave anechoic chambers.